(untitled) (International Journal of Engineering and Computer Science, 2018)
In this paper we are going to present about Agriculture Robot how farmer can perform plowing, seeding and grass cutting in fields. To perform this operation by using the agriculture robot we can reduce the labor work. We are using the android application to provide the input to the robot. By using GSM we are going to communicate with the robot. This system has three main sections like seeding, plowing and waste plant cutting. As per the user instruction the robot will perform the operation without human presence. It automatically stops when there is any abstracal comes in between and it sends the message regarding the abstracal to the user. By using, ultrasonic sensor it detects the abstract which comes in front of the robot.